Pineapple Leaves Box: For Cosmetic Product - Wan Mohd Zain, Wan Zuraida; Hamid, Nur ‘Amira; Nor Azmee, Nazatul Nazihah; Kamisan, Nurfarahani; Ismail, Nor Afiqah (Multidisciplinary Applied Research and Innovation, 2021)
Ananas comosus, or pineapple, is a common tropical plant with coalesced berries. Pineapple leaf fibres have a high potential for use as an alternative raw material in the box industry due to their mechanical properties, renewable resource, and low cost fibres. The study's main objectives are to look into the requirements for using and improving natural cellulosic plant fibres in pulping and box production, to recognize the various issues associated with using natural plant residues in pulp and box production, and to look into the prospects of various natural cellulosic plant fibres for pulp and box production. Pineapple leaves were pulped using a chemical pulping method called soda pulping, and the pulp obtained was tested for chemical composition, which included lignin content (11.5%), ash content (1.2%), pulp yield (15%), and cellulose content (65%) for pineapple leaves. Overall, the results showed that pineapple leaves have a lot of potential as pulp and box fibre alternatives. This pineapple leaves box can be a very useful product in the long run because the majority of respondents agree that this product will be standing in the future especially in minimizing the problem of the post-harvest agricultural system in the pineapple sector in Malaysia.